62.3k views
3 votes
How do you substitute 3x-12y=-6 and x-4=-8?

User Mshildt
by
5.2k points

1 Answer

5 votes

x - 4 = -8 add 4 to both sides

x = -4

Put the value of x to the first equation 3x - 12y = -6:

3(-4) - 12y = -6

-12 - 12y = -6 add 12 to both sides

-12y = 6 divide both sides by (-12)

y = - 0.5

Answer: x = -4 and y = -0.5

New question:

x - 4y = -8 add 4y to both sides

x = 4y - 8

Substitute it to the first equation:

3(4y - 8) - 12y = -6 use distributive property

(3)(4y) + (3)(-8) - 12y = -6

12y - 24 - 12y = -6

-24 = -6 FALSE

Answer: No solution.

User MaxRocket
by
4.9k points